دور الميزة النسبية في تحقيق أهداف المحتوى المحلي وفق رؤية المملكة العربية السعودية 2030م تمور عجوة المدينة أنموذجاً : The Role of Comparative Advantage in Achieving Local Content Objectives under Saudi Vision 2030: Ajwa Dates of Medina as a Model. - حامد بن مزيد بن حامد الحربي (Journal of North African Economies, 2025)
This research examines how Medina’s Ajwa dates can be used to enhance local content in Saudi Arabia, supporting the goals of Vision 2030. The study highlights Ajwa’s unique religious, nutritional, and health benefits, and its potential to drive economic gains. Key Findings: Distinct Comparative Advantage: Ajwa dates’ religious, nutritional, and health value support local content and align with Vision 2030. Agricultural Challenges: Limited land and climate impacts require sustainable farming methods that conserve water. Awareness and Infrastructure: Low global awareness and high storage costs hinder exports; marketing and improved infrastructure are needed. Product Innovation: Developing Ajwa-based products can boost demand locally and internationally. Brand Identity: A strong brand, emphasizing quality and cultural value, can elevate Ajwa dates globally.